World development report 1982 - World Bank (Washington D.C.: Oxford University Press, 1982)
This fifth World Development Report, 1982 focuses on International Development Trends; Agriculture and Economic Development and World Development Indicators.
rpm 08/02/2019
Ref.
Keywords: Economic Development; Economic history; Economic policy; Power resources; Underdeveloped Countries